Synopsis: Rwanda smallholder agricultural commercialization survey: Overview using selective categorical variables - Warner, James; Rosenbach, Gracie; Benimana, Gilberthe Uwera; Mugabo, Serge; Niyonsingiza, Josue; Mukangabo, Emerence; Dushimayezu, Bertrand; Nshimiyimana, Octave; Ingabire, Chantal; Spielman, David J. (International Food Policy Research Institute, 2024)
Increased commercialization of smallholder farmers is a major emphasis of Rwanda’s PSTA4 and will continue with PSTA5, as well as other policy documents related to agriculture. Although PSTA4 sought to increase the profitability of smallholder production, efforts to address accelerating commercialization were limited due to the absence of data and analysis on returns to commercial production systems. Relatively little was known about smallholder agricultural decision-making and the associated costs and returns to production systems among these farmers. This policy note introduces an important research initiative that will explore various aspects of commercialization by Rwandan smallholder farmers and is meant as a general introduction to smallholder commercialization. In subsequent research papers, more detailed studies based on these initial findings will contribute to an improved understanding of agricultural smallholders by providing (1) more nuanced analysis of commercial farmer typologies, (2) estimates of returns to commercial production systems across multiple farmers typologies, and (3) recommendations designed to improve interventions in smallholder commercialization.